(untitled) (SAARC Journal of Agriculture, 2022)
Pea (Pisum sativum L.) is the most important grain legume crop grown worldwide and used as food and fodder. An experiment was undertaken to elucidate the genetic variability in five inbred parents and their 17 F4’s derivatives in pea evaluating ten characters during the winter season of 2017-2018 at the research farm, BSMRAU, Gazipur, Bangladesh. Analysis of variance explored significant differences among the genotypes for all the characters. Phenotypic coefficients of variation were close to genotypic coefficients of variation for all the characters indicating less influence on the environment and potentiality of selection. High heritability associated with high genetic advance was observed for plant height, pod per plant, hundred seed weight, and seed yield per plot. Days to 50% flowering and days to first flowering showed a highly significant positive correlation at both genotypic and phenotypic levels. Plant height showed a highly significant positive correlation with pods per plant, seeds per pod, and seed yield per plant. Pod length showed a highly significant positive correlation with pod width and hundred seeds weight. Pods per plant, pod width, and seeds per pod showed a highly positive correlation with seed yield per plant and 100-seed weight. Only days to first flowering showed a highly negative correlation with pod length and hundred seed weight. Path coefficient analysis revealed that plant height, pod per plant, and seeds per pod had a highly positive effect on yield per plant. Therefore, the yield improvement of pea is plausibly possible by associating and selecting those plant traits. Furthermore, two crosses such as Zhikargacha×IPSA Motorshuti 1 and Zhikargacha×IPSA Motorshuti 2 may be chosen for further breeding programs. SAARC J. Agric., 20(1): 29-39 (2022)